ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BELI KONSUMEN PADA LAYANAN ONLINE TRAVELOKA - Suali; Simanjuntak, Jackhon Pahala (ADAI Kepri, 2023)
Traveloka is the fastest, cheapest and most comprehensive airlineticket search site. The prices displayed on the Traveloka website havebeen processed from a network of official sources. The purpose of thisstudy was to determine the effect of brand image, price, and trust inconsumer buying interest in Traveloka Online services. The populationin this study are consumers who have used Traveloka Online services.The number of samples in this study were 100 respondents with asimple random sampling technique. The data analysis technique in thisstudy uses multiple linear regression analysis, classical assumptiontest, statistical test. The results of this study indicate that brand image,price, and trust simultaneously have a significant effect on buyinginterest in Traveloka Online services. Partially the brand image andprice do not significantly affect the interest in buying Traveloka Onlineservices and Trust partially significantly affects buying interest inTraveloka Online services. In implementing the marketing strategy, itfurther increases trust, given that consumer trust in traveloka has notbeen well embedded. This can be done for example by way of makingthe design more interesting, easy to understand, and responsible forevery problem